Influence of synthetic antioxidants on the oxidation stability of biodiesel produced from acid raw Jatropha curcas oil - Supriyono; Sulistyo, Hary; Almeida, Manuel F.; Dias, Joana M. (Fuel processing technology, 2015)
In the present work, Jatropha curcas biodiesel was produced from a high free fatty acid raw oil (AV=35.36mg KOH g−1) containing 76.5% w/w of unsaturated fatty acids. The production route consisted of a two-step method, using acid esterification, followed by conventional alkali methanolysis. Biodiesel was characterized in agreement with EN 14214:2014 and a study on the use of 4 synthetic antioxidants was conducted. The high free fatty acid content of the oil could be reduced to 0.8% w/w by acid esterification. A good product quality was generally observed but the very low oxidation stability, corresponding to an induction period (IP) of 1.37h, was the highest concern. Statistically significant predictive models, which related each antioxidant concentration with the IP, were obtained. Pyrogallol (PY) showed the best results, being estimated that the use of 204ppm in biodiesel could increase its IP to the limit imposed by the quality standard (8h). The following rank, in terms of effectiveness, was obtained: PY>propyl gallate (PG)>butylated hydroxytoluene (BHT)>tert-butyl hydroquinone (TBHQ). In agreement, the stabilization factors (F), considering the use of 204ppm of antioxidant, were: 5.84 for PY, 4.06 for PG, 1.85 for BHT and 0.85 for TBHQ. •Jatropha curcas biodiesel was produced from a raw high free fatty acid oil.•Acid esterification allowed the reduction of the free fatty acid content from 18%w/w to 0.8%w/w.•Biodiesel produced presented very low oxidation stability (IP=1.37h).•Effectiveness of antioxidants: PY>PG>BHT>TBHQ.•Predictive models were established and using around 200ppm of PY it is possible to achieve an IP of 8h.